A Preliminary Exploration of Declarative Intonation in the Chilean Diaspora of Sweden - Brianna Butera; Rajiv Rao; Maryann Parada (Languages, 2023)
Motivated by a growing body of research on heritage Spanish prosody, the current study uses the Sp_ToBi framework for the transcription of Spanish intonation to report trends in phonological targets of broad focus declaratives produced by heritage speakers of Chilean Spanish living in Stockholm, Sweden. Data were collected via semi-structured interviews from six participants belonging to the same social network including two Spanish-dominant first-generation immigrants and four Swedish-dominant second-generation speakers who were born and raised in Sweden and are heritage speakers of Spanish. The G1 participants are the primary source of Spanish input for the G2 speakers. Data were analyzed by identifying word- and phrase-level phonological targets and associating them with the appropriate pitch accent and boundary tones. Results show that the heritage Spanish declarative intonation patterns of the G2 speakers closely resemble those of the G1 speakers. These patterns are scrutinized in terms of the potential influence of Swedish and/or other varieties of Spanish. This analysis exhibits evidence of the importance of source input variety and cross-generational transmission of phonological targets in a heritage language as well as the potential contributions of multiple intonational systems in forming the phonological inventory of heritage speakers.